Therapeutic potential of Bacopa monnieri extracts against hepatocellular carcinoma through in-vitro and computational studies - Awais Altaf; Asia Kiran; Muhammad Sarwar; Tahir Maqbool; Sumaira Sharif; Hana’a Iqbal; Saba Farooq; Qurban Ali; Shiming Han; Ajaz Ahmad (PLoS ONE, 2025)
Background Among various cancers, primary liver cancer is the seventh most diagnosed malignancy and is the second most prevalent contributor to cancer-causing deaths. During conventional treatment, the recurrence of disease, low drug inefficacy, and severe side effects are the main limitations. Recently, natural anticancer medicines from the Middle East, Korea, China, Europe, North America, and India have attracted a lot of interest due to their low side effects and better remedial properties. The current study investigated the antioxidative and anticancer effects of ethanolic (BME) and n-hexane (BMH) extracts of B. monnieri (L.) Wettst. Methods In the current study, phytochemical profiling was done using gas chromatography-mass spectrometry (GC-MS) analysis. The antioxidant potential was measured using DPPH, nitric oxide, superoxide anion, and hydrogen peroxide assays, while the cell viability and apoptotic effect were measured by MTT, crystal violet, and annexin V/PI protocols, respectively. Results Higher concentrations of total phenolic contents (274.92±3.52 mgGAE/g), total flavonoid contents (141.99±4.14 mgQE/g) and tannins (55.49±4.63 mgTAE/g) were observed in BME extract with strong antioxidant potential than BMH extract. Also, BME extract showed higher cytotoxicity with less IC50 value (24.70 μg/mL) and a lower percentage of cell viability, while the same extract exhibited 58.65% apoptosis against HepG2 cells in comparison to cisplatin and BMH extract. Furthermore, Spiro[(tricyclo[6.2.2.0(2,7)]dodeca-5,9-diene)-4,1’-cyclobutane]-11,2’-dione from BME extract showed the lead docking score of -8.8, -8.1 and -7.8 kcal/mol against TGF-βR1, TNF-α, and iNOS, respectively. Conclusion In conclusion, the ethanolic extract of B. monnieri has a significant potential for becoming a potent anticancer drug that effectively treats liver damage, including HCC.